Equalisation Transfers and Local Fiscal Capacity: A New Methodology for Ireland - Turley, Gerard; McNena, Stephen (The Economic and Social Review, 2021)
Fiscal equalisation is a key element of a country’s fiscal arrangements where functions and funding are decentralised to subnational government. Although Ireland’s horizontal fiscal imbalances are partly reduced by grants from an equalisation fund, the current model of equalisation payments is not fit for purpose. In this paper, we design a new fiscal equalisation system for Ireland’s 31 local authorities based on a Representative Revenue System model and estimates of fiscal capacity. Using the main revenue sources, we estimate fiscal capacity for 2017, and calculate formula-derived equalisation transfers for the financially weaker local councils. Compared to the existing transfers funded from the local property tax, our results provide for a larger equalisation fund financed by the central government, a greater degree of equalisation but with individual council winners and losers. Careful consideration needs to be given to the funding options available to the net losers, including higher taxes locally levied on commercial and/or residential properties, or where deemed necessary, a temporary transition payment from the central government.